Drug Repurposing for the Discovery of Potential Inhibitors Targeting DJ-1 (PARK7) Against Parkinson’s Disease - Taibah Aldakhil; Ali Altharawi (Crystals)
Parkinson’s disease (PD) is a neurodegenerative disease characterized by increased movement dysfunction and cognitive loss. DJ-1 (PARK7) is an antioxidant that protects cells from oxidative stress, a major contributor to cellular damage and neurodegeneration in PD. Mutations in the DJ-1 gene reduce its neuroprotective ability contributing to PD onset and progression. The neuroprotective and antioxidant properties of DJ-1 make it a viable therapeutic target for developing novel PD therapeutics. A drug repurposing approach was applied to identify promising inhibitors for DJ-1. Three drugs—droxicam, pteroylglutamic acid, and niraparib—were identified based on their binding affinities and interactions. Further molecular dynamics simulations revealed that niraparib and pteroylglutamic acid were the most stable among the three complexes. Moreover, the binding strength of the complexes was confirmed by MMPBSA binding free energy analysis, with Niraparib (−13.50 kcal/mol) and pteroylglutamic Acid (−11.41 kcal/mol) as the most promising candidates. These results suggest that pteroylglutamic acid and niraparib may serve as useful DJ-1 inhibitors for PD-associated protein DJ-1. Further experimental validation and in vivo assessments are required to confirm the efficacy and safety of these drugs against PD.